THE IMPACT OF BUSINESS ENVIRONMENT ON STRATEGIC DECISION MAKING IN RETAIL INDUSTRY AT MAKASSAR CITY - Siti Nurjannah Saleba; Musran Munizu; Nurjanna Hamid (Jurnal Ekonomi, 2023)
The purpose of this study was to determine whether there is an influence of internal environment, external environment to strategic decision making in retail industry at Makassar city. The sample of this research was 85 owner or manager minimarket retail. The method used in this study is quantitative method with multiple linear regression analysis techniques. The data used are secondary data and primary data, hypothesis testing uses the coefficient of determination test (R²), hypothesis F Results, and hypothesis T Results.